Pengembangan Ekonomi Masyarakat Desa Alassapi Berbasis Moderasi Beragama Menuju Kesejahteraan Masyarakat - Maula, Noer Hibbatul; Ayu, Fanila Riska; Lailiyah, Dewi Nur; Hanani, Sofiatul; Musrifa, Musrifa; Maimunah, Putri; Prastiwi7, Ayu Ariska (Najah: Journal of Research and Community Service, 2024)
This service aims to develop the community economy in Alassapi Village by adopting a religious moderation approach, with the main focus on improving community welfare. Through this approach, various economic empowerment activities are carried out such as skills training, micro business development, and promotion of entrepreneurship based on moderate religious values. The research methods used include literature studies, field surveys, and active community participation. The results include an increase in community income, diversification of income sources, and an overall improvement in the quality of life. Thus, this service not only provides a positive economic impact, but also contributes to the creation of social harmony and general welfare in Alassapi Village.